2021
DOI: 10.3390/met11020338
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of 7075 and 7049 Aluminium Alloys Intended for Extrusion Welding

Abstract: During the extrusion of aluminum alloys profiles using porthole dies, the temperature of the material in the welding chamber is one of crucial parameters determining the quality of longitudinal welds. In order to extend the permissible temperature range, the billets intended for this process should be characterized by the maximum attainable solidus temperature. Within the present work, the homogenization of AlZnMgCu alloys DC-cast (Direct Chill-cast) billets was investigated, with the aim of solidus temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Since the homogenization temperature was high enough to dissolve the η-phase, we can assume that these grain-boundary precipitates are S-phase. This confirms that, on the one hand, the S-phase remains after quenching the samples into water [ 40 ]. Therefore, a higher temperature or longer homogenization time is needed to eliminate the S-phase.…”
Section: Resultssupporting
confidence: 81%
“…Since the homogenization temperature was high enough to dissolve the η-phase, we can assume that these grain-boundary precipitates are S-phase. This confirms that, on the one hand, the S-phase remains after quenching the samples into water [ 40 ]. Therefore, a higher temperature or longer homogenization time is needed to eliminate the S-phase.…”
Section: Resultssupporting
confidence: 81%
“…Many researchers have analyzed and concluded the incorporation of hard ceramic materials into soft materials improves tribological properties. SiC-reinforced Al7050 MMC [47], grapheneincorporated Al7075 MMC [48,49], Al 2 O 3 -reinforced Al7075 MMC [50], SiC-reinforced Al7075 [51,52], 7.5% SiC-reinforced Al6061 MMC [53], and TiC-reinforced Al6070 MMC [54] were subjected to wear analysis using the Taguchi method and the results concluded that particles addition improved the wear resistance of the composite materials compared to the base metal, and also the sliding distance mostly influenced the wear property.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…The S, T, and η phases described in the literature are solid solutions with extended composition ranges, containing all four elements. It should be noted that the literature data clearly indicate that the mentioned phases are lowmelting, especially η-MgZn2, and their presence causes a significant decrease in the solidus temperature, even below 480 • C for the 7075 alloy [12,13]. It causes a large difference between the liquidus and solidus temperatures, which in turn leads to the need to lower the temperature of plastic-forming processes.…”
Section: Introductionmentioning
confidence: 97%
“…The distinctive feature of that process is directional crystallization, taking place from the outer zones (intensively cooled zones near the crystallizer) to the center of the ingot. As a result, a dendritic structure is formed [12]. Dendrites from the Al-rich α phase grow along the temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation